Secret Partners : Big Tom Brown and the Barker Gang - Mahoney, Timothy, 1947- (Book collections on Project MUSE., 2013)
Among the most dangerous criminals of the public enemies era was a man who has long hidden in history's shadows: Tom Brown. In the early 1930s, while he was police chief of St. Paul, Minnesota, Brown became a secret partner of the infamous Barker gang. He profited from their violent crimes, he protected the gang from raids by the nascent FBI--and while he did all this, the gangsters gunned down cops and citizens in his hometown.